Direct immersion dual-drop microextraction for simultaneous separation and enrichment of Cr(III) and Cr(IV) in food samples prior to graphite furnace atomic absorption spectrometry detection. (16th April 2023) - Yan, Juntao; Zhang, Chenghao; Wang, Chunlei; Lu, Dengbo; Chen, Shizhong
Highlights: Direct immersion dual-drop microextraction (DIDDME) was firstly developed for Cr species. Cr(III) and Cr(VI) were separated and enriched into two drops at pH 3.5, respectively. DIDDME did not require tedious oxidation/reduction or centrifugation/filtration steps. This method avoided risk of sample contamination and analysis errors in redox speciation strategies. Ingenious use of DIDDME made separation of Cr(III) and Cr(VI) convenient, efficient and time-saving. Abstract: Non-chromatographic speciation methods generally involve speciation conversion, which may cause sample contamination, analysis errors and tedious operations. In this work, a direct immersion dual-drop microextraction (DIDDME) was firstly developed for separation and preconcentration of Cr(III) and Cr(VI). In DIDDME, two organic drops on needle tips of microsyringes were concurrently immersed in a stirred sample solution. Each drop contains a chelating reagent for reacting with a specific species. Thus, Cr(III) and Cr(VI) were selectively extracted into different drops. This method afforded detection limits of 3.0 and 4.1 ng/L, quantification limit of 10 ng/L and 14 ng/L, linear range of 0.01–30 ng mL −1 and enrichment factors of 354-fold and 326-fold for Cr(III) and Cr(VI), respectively. Precisions like repeatability and reproducibility were assessed by calculating relative standard deviations, which were lower than 5.4 % and 6.9 %, respectively. This procedure was used successfully for quantification of Cr(III) and Cr(VI) in food samples.